Fast generative tool for masonry structures geometries - Savalle, Nathanaël (2021)
Modelling masonry bond pattern is still challenging for the scientific community. Though advanced Laser Scanning methods are available and allow to extract blocks sizes and shapes of actual masonry structures, they are up to now very time-consuming and complex to set up. Therefore, modelling masonry as an ideal and regular assemblage of regular units is still very common in the scientific field. This paper presents a generative algorithm for masonry specimens built with a single-leaf cond pattern. It is based on C# programming under the environment offered by Rhinoceros (+ Grasshopper). Five components have been constructed (wall, corner, T and cross-connections, and opening). They can be assembled, up to infinity, to build complex masonry specimens. Moreover, they are all parametrised to account for every wish of the modeller. The global methodology is found highly time-efficient, with the creation of an initial geometry composed of 5 – 10 components requiring around 10 minutes and, while the update due to a parameter variation is done in less than one second. The paper finally discusses the next developments of the promising generative algorithm.